ASSOCIATIVE PLOT IN THE NOVEL (Scientific journal of the Fergana State University, 2023)
The article reveals the associative form of the plot of the novel, its features in the genre of the novel. The conflict in novels is based on the method of associative plot, its specificity is analyzed through examples.